Prevalence and determinants of inadequate dietary diversity among pregnant women in four Sub-Saharan Africa countries: a multilevel analysis of recent demographic and health surveys from 2021 to 2022 - Zegeye, Alebachew Ferede; Mekonen, Enyew Getaneh; Tamir, Tadesse Tarik; Workneh, Belayneh Shetie (Frontiers in Nutrition, 2024)
Background Diversity in the mother’s diet can have major effects on the developing fetus throughout pregnancy. Approximately 1 million neonates die on their first day of life as a result of inadequate nutrition, which also complicates the mother’s pregnancy and has a negative impact on the delivery outcome. Dietary diversity during pregnancy is poorly recognized in developing countries, despite the fact that it is detrimental. As a result, this study aimed to assess the prevalence and associated factors of inadequate dietary diversity in Burkina Faso, Ghana, Kenya, and Tanzania among pregnant women. Methods Secondary data analysis was conducted using data from the most recent Demographic and Health Surveys, which included four countries in Sub-Saharan Africa between 2021 and 2022. A total of 80,083 pregnant women were included in this study. The women’s dietary diversity was computed from 10 food categories. Based on the minimum diversity score, women were categorized as having inadequate dietary diversity if their diversity score was less than five food items and as having adequate dietary diversity if they took five or more food groups. A multilevel mixed-effects logistic regression model was used to identify the factors associated with inadequate dietary diversity. At p-values <0.05, significant factors correlated with inadequate diversity were identified. The result was interpreted using 95%CI and adjusted odds ratio. The best-fit model was determined to be the one with the lowest deviance and highest loglikelihood ratio. Results The prevalence of inadequate dietary diversity among pregnant women in Burkina Faso, Ghana, Kenya, and Tanzania was 94.46%. Factors such as no formal education (AOR = 3.39, 95% CI: 2.54, 4.54), distance to health facilities (AOR = 1.36, 95% CI: 1.16, 1.60), poor wealth quantiles (AOR = 2.97, 95% CI: 2.41, 3.65), no media exposure (AOR = 1.84, 95% CI: 1.45, 2.35), low community ANC utilization (AOR = 1.21, 95% CI: 1.16, 1.60), and reside Burkina Faso (AOR = 1.47, 95% CI: 1.09, 1.99) were among the factors associated with inadequate dietary diversity. Conclusion According to this study finding, pregnant women had a high percentage of inadequate dietary diversity. Factors at the individual and community levels contributed to the lack of diversity in nutrition. Thus, when developing policies and strategies, the health ministries of Burkina Faso, Kenya, Ghana, and Tanzania should to consider the women who underutilize antenatal care services, live in low wealth quantiles and who did not get formal education.